Life Cycle Assessment of Alternatives for Industrial Textile Recycling - Vasquez-Perez, O; Espinoza-Perez, A; Espinoza-Perez, L (Elsevier B.V., 2024)
The $882 billion textile trade in 2021 poses environmental concerns, highlighting the importance of encouraging a circular economy to attain sustainable textiles. Therefore, policies must prioritize textile recycling, particularly in developing countries, and sharing information throughout the value chain. This research aims to explore the potential environmental benefits of two industrial recycling processes for textile residues versus the traditional waste management and production process through a life cycle assessment applying the ReCiPe method at midpoint and endpoint levels focusing on generating significant data availability and broader assessment than existing literature to support decision making related to recycling systems for textile residues. Results related to the textile residues recycling process to obtain stripes (R1) and replace sawdust, to fill pushing balls, show that it would produce environmental benefits regardless of location in several midpoint categories. Furthermore, regarding the endpoint results, the DALY savings are mainly due to avoiding landfill, while the savings in ecosystem impacts are generated by avoiding landfill and sawdust production. Regarding the recycling process to obtain recycled yarn and fill (R2) net savings in global warming potential are generated if landfill avoidance is considered. Nevertheless, endpoint results show that DALYs of all the avoided processes correspond to 1.5 times the impacts of all the R2 recycling processes, mainly due to avoiding virgin yarn production. Therefore, both recycling processes are recommended. However, some strategies are required to generate greater benefits, such as applying the R2 recycling process as the first option for stretchable textile waste, and after being used, going through the R1 recycling process. In addition, the strategic placement of the R1 recycling facility should be distant from areas of sawdust production. A sensitivity analysis was carried out due to the variability of virgin products to replace in the market. © 2024 Elsevier B.V.